DAMPAK PANDEMI COVID-19 PADA PROSES PEMBELAJARAN DI MI AL AMIN DESA SUMBERSARI KECAMATAN SRONO - Permadi, Benny Angga; Ihsan, Moh. Hayatul; Rofiudin, Moh. (PGMI Department of Institut Agama Islam Ibrahimy Genteng Banyuwangi, Indonesia, 2022)
This study aims to reveal the impact of the Covid-19 pandemic on the learning process at MI Al Amin Sumbersari. This type of research is an exploratory case study with a qualitative approach. The data used in the study was primary data obtained from semi-structured interviews with a list of questions compiled based on related literature. Respondents interviewed from a total of 180 students consisted of 30 students along with student guardians and 6 teachers. The data collection techniques used are interviews, questionnaires and documentation. While the data analysis technique used is a thematic analysis technique. The results of research on the impact of the pandemic on the learning process at MI Al Amin Sumbersari showed that 60% of students were affected and 40% of students were not affected. Meanwhile, 66% of student guardians were affected and 34% of student guardians were not affected. In addition, 66% of teachers were affected and 34% of teachers were not affected.